Children in Need of Medical Innovation - Horst Entorf; Jörg Fegert; Michael Kölch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
As the innovation process of pharmaceuticals is a long, risky and very costly business, economists typically emphasise lack of profit incentives and small market size as the most important obstacles to child-related innovative activity. Moreover, there are ethical concerns because children are not able to give their ?informed consent? to requested clinical trials. Thus, economic incentives, legal restrictions and ethical concerns seem to be responsible for the lack of innovative activity targeted at drugs for children, though social costbenefit considerations (i.e. welfare analysis) would most probably predict a high gain from the introduction of critical innovations. Grounded on a highly interdisciplinary view based on medical, pharmaceutical and economic research, this survey aims at analysing channels of influence that might be helpful both in the analysis of the innovation process of drugs for children, and in improving the uncertain situation of pediatric therapy.
Keywords: 330; Pharmazeutische Forschung; Kinder; Medizin; Innovation; Marktversagen; Kosten-Nutzen-Analyse